2010
DOI: 10.1016/j.joca.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Hip strengthening reduces symptoms but not knee load in people with medial knee osteoarthritis and varus malalignment: a randomised controlled trial

Abstract: ACTR12607000001493.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
229
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(247 citation statements)
references
References 45 publications
10
229
2
6
Order By: Relevance
“…Similarly, a recent RCT with 54 female patients with knee OA, showed that a 6-month highintensity progressive lower limb resistance training program did not reduce the knee adduction moment (KAM), an indirect measure of compartment-specific knee load, compared to a sham exercise program [21]. This lack of effect of exercise on knee load is consistent with previous RCTs evaluating quadriceps [22] and hip muscle [23] strengthening in people with knee OA. Thus, while exercise can reduce symptoms, there is currently little evidence to suggest that exercise can be disease-modifying in people with knee OA.…”
Section: Exercise Is Integral In Managing Knee Oasupporting
confidence: 79%
“…Similarly, a recent RCT with 54 female patients with knee OA, showed that a 6-month highintensity progressive lower limb resistance training program did not reduce the knee adduction moment (KAM), an indirect measure of compartment-specific knee load, compared to a sham exercise program [21]. This lack of effect of exercise on knee load is consistent with previous RCTs evaluating quadriceps [22] and hip muscle [23] strengthening in people with knee OA. Thus, while exercise can reduce symptoms, there is currently little evidence to suggest that exercise can be disease-modifying in people with knee OA.…”
Section: Exercise Is Integral In Managing Knee Oasupporting
confidence: 79%
“…Dynamic knee alignment can be assessed using 3-D gait analysis. In varus knees the measurement of knee adduction moment during stance phase of walking is an indirect measure of joint compressive forces sustained within the medial tibiofemoral joint compartment (49,52,53). Static and dynamic alignment are important to consider in view that altered distribution of forces placed through the joint surface may lead to damage of articular structures, possibly increasing risk of OA development or worsening existent disease.…”
Section: Muscle Strengthmentioning
confidence: 99%
“…Indeed, focusing on hip abductor muscles training may represent an effective option to reduce external adduction knee moment and the knee pain score of patients. The same year, a randomized study of Bennell, et al (2010) [8] confirms that strengthening the hip muscles improves symptoms and knee OA function but does not affect the medial knee loading measured by the adduction moment, nor does it affect the progression of the pathology. Research is still necessary to develop optimal physiotherapy programs for knee OA patients.…”
Section: Resultsmentioning
confidence: 86%
“…[7] They also demonstrated that strengthening hip muscles reduced symptoms and improved the function of the OA patient's knee. [8] We found one study looking at the link between biomechanical changes at the knee, the hip, and the ankle in 2008. [9] The authors measured the knee and hip moments using an inverse dynamic model after gait analysis with skin markers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation